Édouard Glissant : entre l’insularité et la pensée archipélique - Obszyński, Michał (Romanica Silesiana)
The goal of this paper is to show how Édouard Glissant’s understanding of Antillean culture and literature evolve from the project of antillanité to the idea of creolization. The former (put forward in Le discours antillais published in 1981), bears the mark of an “insular” perception of the West Indies, but it simultaneously gives birth to some concepts stressing a relational character of the Antillean social and cultural reality. In a more detailed and elaborated form, this “archipelagic” perspective will be in the very center of Glissant’s aesthetic program presented in Poétique de la relation (1990) and Traité du Tout‑monde (1997), which extend the range of analyzed issues in order to encompass the globalization phenomenon. Key words: creolization, postcolonial literature, Caribbean literature, Édouard Glissant, antillanité, cultural transfers, literature and globalization